BIPOLAR DISORDER EPISODES IN THE PROTAGONIST OF JENNIFER NIVEN’S ALL THE BRIGHT PLACES - Ikbal, Muhammar; Pawiro, Muhammad Ali (Universitas Islam Sumatera Utara, 2024)
This study investigates the depiction of bipolar disorder in Jennifer Niven’s All the Bright Places, focusing on its impact on the protagonist, Theodore Finch. Using a psychological framework, the research draws on Lesmana’s theory of bipolar disorder to analyze the manic and depressive episodes Finch experiences throughout the novel. The narrative vividly portrays Finch’s drastic mood swings, alternating between periods of elevated euphoria and profound depression. This analysis examines how these emotional extremes shape Finch's interactions with others, influence his relationships, and contribute to his suicidal thoughts. Through a deep dive into Finch’s character, the study emphasizes the challenges of living with bipolar disorder, illustrating how the disorder affects both personal identity and social dynamics. The findings reveal that Finch's experiences align with the characteristic patterns of manic and depressive episodes, as outlined in Lesmana’s theory. Ultimately, the research highlights the importance of addressing mental health issues in literature, enriching the conversation on psychological themes and fostering greater empathy for those affected by such conditions.